Strategic planning : balancing short-run performance and longer term prospects. - Veliyath, Rajaram (1992)
Explains that strategic planning activities can, to varying degrees, be anticipatory or hindsight in orientation. Anticipatory activities prepare the firm for future strategic surprises, while hindsight activities seek remedial measures after events have occurred.